Protection and Preservation of the Marine Environment Through a Marine Ecotourism Scheme in Nusa Penida Bali - Banna, Sabri; Taher, Tarmizi; Pradana, Aditya Bagus (Indonesian Journal of Environmental Law and Sustainable Development, 2023)
This study examines the potential of a marine ecotourism scheme as a strategy for the protection and preservation of the marine environment in Nusa Penida, Bali. With the rapid growth of tourism in the region, there is an urgent need to balance economic development with environmental conservation efforts. Through qualitative research methods, including interviews, surveys, and site observations, this research explores the current state of the marine environment in Nusa Penida and assesses the feasibility and effectiveness of implementing a marine ecotourism scheme as a means of sustainable development. The findings reveal significant threats to the marine environment in Nusa Penida, including coral reef degradation, marine pollution, and habitat destruction. However, the study also identifies opportunities for conservation and sustainable management through the promotion of marine ecotourism initiatives. By engaging local communities, businesses, and government agencies in collaborative conservation efforts, a marine ecotourism scheme has the potential to generate economic benefits while simultaneously safeguarding marine biodiversity and ecosystem health. This research contributes to the growing body of knowledge on sustainable tourism development and provides practical recommendations for policymakers, stakeholders, and practitioners seeking to promote the protection and preservation of marine environments in coastal regions like Nusa Penida, Bali.